Magico-religious Beliefs in Schizophrenia: A study from Eastern part of Nepal - Sapkota, Nidesh; Shakya, Dhana Ratna; Adhikari, Baikuntha Raj; Pandey, Arun Kumar; Shyangwa, Pramod Mohan (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: Schizophrenia is one of the commonest psychiatric disorders which require immediate interventions. Magico-Religious beliefs may affect the expression of psychopathology as beliefs are entrenched into human psyche. Local and community beliefs in such phenomena appeared to be a factor in influencing the decision to seek magico-religious treatment. This study aimed (1) to determine attitude of patients and relatives with respect to magico-religious beliefs and its influence on psychopathology, and (2) to examine the relationship between psychopathology and major sociodemographic variables. Materials & Methods: All 50 consecutive cases of schizophrenia attending psychiatric services during study period were thoroughly evaluated. All the cases were diagnosed as per ICD 10 DCR criteria. The supernatural attitude questionnaire was applied. Results: Fifty cases were studied. Among them, 48% belonged to the age-group of 25 to 34 years, the majority of them were male (62%), 82% were Hindus, and 64% married. Majority of the patients had undergone magico-religious treatment (n = 35). Among the sample, 68% consulted faith healer and 42% performed religious treatment during the illness period; 60% acknowledged personal belief in sorcery, 58% in ghosts, and 52% in spirit intrusion. Among them, 20% believed there was a link between sorcery and mental illness, and 20% believe spirit could cause mental illness. Among the samples, 38% found the link between sorcery and abnormal behaviour, 38% with evil spirit, and 22% due to planetary influences. Statistically significant association was noted in the belief that rituals can improve patient behaviour and local belief in supernatural influences. Conclusion: There is a common belief in the relationship between supernatural influences and mental illness among the relatives of the patients. Such beliefs and magicoreligious treatment do occur during the course of the illness.